58.4: A Novel Handling Method of Ultra‐Thin Flexible Glass Substrate for Thin and Flexible Displays. Issue 1 (1st July 2013) - Chen, Ru‐De; Yuan, Shuo‐Huang; Hsu, Hsin‐Yun; Lu, Luke
Abstract: A novel handling method of ultra‐thin flexible glass substrate (UTFGS) for thin and/or flexible displays is proposed. A rigid glass carrier‐attached UTFGS (UTFGS module) with no adhesive layer is proposed for its good thermal and chemical durability. These UTFGS module can be processed through conventional display manufacturing process, such LCDs or OLEDs, and also can be mechanically and easily detached from the carrier substrate. Therefore this method enables to manufacture fragile, thin and flexible displays using conventional manufacturing equipment for LCDs or OLEDs, without chemical and/or mechanical thinning of thick display‐cells and also without using of roll‐to‐roll process equipment for manufacturing of flexible displays.